THE IMPLEMENTATION OF WHO MHGAP PRINCIPLES WITHIN EDUCATIONAL SYLLABUS OF YEREVAN STATE MEDICAL UNIVESITY - Avetisyan , K.S.; Gasparyan, Kh.V. (Modern Psychology, 2020)
In this article wepresent the process of implementation of WHO mhGAPprogram principles and approaches in undergraduate, postgraduate, Ph.D  30 and Continuous Medical Education (CME) curriculum of the M. Heratsi Yerevan State Medical University (YSMU). ForCME we worked out two weeks duration training modules to cover: Child and Adolescent Mental Health (CAMH) and CAMH in Primary Health Care. The activities related to the program implementation are in progress. We preliminary agreed with WHO representatives about the Armenian translation of mhGAP guide. CME department proved the above mentioned curriculums. In collaboration with Family Medicine department of YSMU mhGAP is included in a training program of physicians and nurses of Primary Health Care. In general the feedback of implemented project is highly positive: more than 85% of trainees are finding it very useful.
Keywords: attention deficit and hyperactivity disorder; Mental health; depression; suicide; stress.